Developing Intercultural Sensitivity in Students of Linguistics - Natalja N. Pomuran (Вестник Кемеровского государственного университета, 2019)
The research deals with the specific features of developing intercultural sensitivity in students of Linguistics in a non- linguistic environment. The paper comprises scientific literature analysis on intercultural sensitivity and the factors of its development. Chen and Starosta's five-factor Intercultural Sensitivity Scale, supplemented by a questionnaire, was employed to measure intercultural sensitivity of 1st, 2nd, and 3d year students majoring in Linguistics. The calculations employed the methods of statistical processing of Student T-test and Fisher criterion. The intercultural sensitivity of students was above average (mean value = 89.47), whereas the increase of all components of intercultural sensitivity, except "Interaction confidence", correlated with the level of foreign language proficiency. In addition, senior students revealed more respect for cultural differences, though they were less confident than junior ones. Moreover, the difference between these two components increased from the 1st year to the3d year of study. Finally, interaction confidence increased if students had travelled overseas and had an experience of interaction with culturally different counterparts. The results and conclusions can be used for the design of programs and training courses for translators and teachers of foreign languages in a non-linguistic environment.